THE EARLY MODERN PERIOD: THE TERM AND ITS APPEARANCE IN OCCIDENTAL HISTORIOGRAPHIES - Gloël, Matthias (Revista de Historia Social y de las Mentalidades, 2017)
This article is about the concept of the Early Modern Period. First it defines the limits of this period and the conscience the contemporaries had about living a change of ages, at the beginning as well as at the end of the Early Modern Period. After this we compare in how different ways this period is to be found in the different occidental historiographies and the development they had to get to be a defined period of 300/350 years. We find, that the break between Early Modern and Late Modern Period is much more marked and clearer in some historiographies (such as the French or the Spanish one) than in others (such as the English or the German one). Finally we try to explain why in some historiographies there is a clearer break around 1800 than in others.